The Ecological Status of the Bottom Waters of an Artificial Lake, East Rumbai District, Pekanbaru City, Riau Province, Uses the ABC Curve - Rahmawati, Anisya; Yuliati, Yuliati; Adriman, Adriman (Jurnal Perikanan dan Kelautan, 2025)
Artificial Lake is one of the lakes located in Lembah Sari Village, Rumbai Pesisir District, which was expanded into East Rumbai District on December 30, 2020, with an area of ​​166.40 ha. The various activities in the artificial lake cause a decrease in water quality due to the input of waste dumped into the lake, thus impacting the ecological condition of the biota, one of which is macrozoobenthos. This research aims to determine the environmental status of bottom waters using macrozoobenthos. This research was carried out in July-August 2023 at three stations. The abundance of macrozoobenthos ranges from 115-465 ind/m3, with the species consisting of 2 classes (Gastropoda and Oligochaeta) divided into four families. Generally, the macrozoobenthos found are the Oligochaeta, tolerant class, and the Gastropoda, facultative class. The diversity index for Stations I, II, and III ranges from 1.010 to 1.224, with a medium level of diversity. The ecological quality of the waters in the Artificial Lake based on the ABC Curve method for Stations I, II, and III showed that the seas were lightly polluted. In general, the water quality at Stations I, II, and III is not much different, where the parameters of temperature, brightness, depth, TSS, pH, and DO are still by class II quality standards PP No. 22 of 2021, but the BOD content is high. High BOD values ​​indicate the amount of organic material at each station.